Change of human flourishing during the COVID-19 pandemic in Japan: Results from population-based U-CORONA study - Yukako Tani; Yusuke Matsuyama; Yui Yamaoka; Hanayo Matsukura; Tomoki Kawahara; Takeo Fujiwara (Elsevier, 2023)
Longitudinal change in flourishing during the pandemic of COVID-19 would provide new insight to reveal determinants of well-being. We aimed to describe changes in flourishing during the COVID-19 pandemic in Japan and to examine the association of sex, age, education, and income with changes in flourishing. Utsunomiya COVID-19 seROprevalence Neighborhood Association (U-CORONA) study conducted in October 2020 and November 2021 was used (n = 419 in 2020 and n = 478 in 2021, and n = 327 for both waves). Flourishing was assessed using a 12-item multidimensional flourishing scale including six domains. Change of flourishing was categorized into decreased, unchanged, and increased. Multinomial logistic regression was applied to longitudinal data to estimate the relative risk ratio of increase and decrease in flourishing scores. Cross-sectional analysis showed that the mean score of flourishing was approximately seven in both waves, with no sex differences, but older adults had higher scores than young-aged adults. We found that men were twice as likely to lose their flourishing scores as women and lower levels of education were associated with 2-3 times declining flourishing scores than higher levels of education. Age and income were not significantly associated with the change of flourishing. During the COVID-19 pandemic, flourishing declined, and men and lower-educated people were more vulnerable. In prolonged difficult situations, support for men and less educated people may contribute to the prevention of declining well-being in Japan.